Joe country eaudiobook - Herron, Mick (Slough House, 2019)
If Spook Street is where spies live, Joe Country is where they go to die. In Slough House, the London outpost for disgraced MI5 spies, memories are stirring, all of them bad. Catherine Standish is buying booze again, Louisa Guy is raking over the ashes of lost love, and new recruit Lech Wicinski is determined to discover who destroyed his career, even if he tears his life apart in the process. And with winter taking its grip, Jackson Lamb would sooner be left brooding in peace, but even he can't ignore the dried blood on his carpets. So when the man responsible for killing a slow horse breaks cover at last, Lamb sends his agents out to even the score.